GEOGRAPHIC INFORMATION PRODUCTS AND SERVICES MARKET IN RUSSIA - S. E. Dyba; I. V. Chernova (Наука. Инновации. Технологии)
Introduction: with the advent of geographic information systems in Russia in the early 90-ies of XX century, a dynamically developing market began to form. Today we are witnessing significant transformations in the information sector in General and in the geoinforma-tion sector in particular. At the same time, there are practically no works analyzing the changes in the structure and dynamics of the market of geoinformation products and services in Russia, the demand for directions among employers, the satisfaction of graduates with their education and the overall state of the market, which is structured in three main directions: navigation, Geoinformatics, remote sensing. Materials and methods of research: the information base of the study was the volume of costs for geoinformation services and software in the context of the subjects of Russia. Site-based www.zakupki.gov.ru [2] intraregional expenditures for geographic information services, software and equipment in 2006 - 2017 were calculated. Research results and their discussion: the register of the most popular educational institutions training specialists in the field under consideration is compiled. There are 3 types of institutions, which are training programmes in the field of cartography, Geoinformatics and geodesy with high ratings, as well as the characteristic uniformity of this educational network in Russia. In addition, the article compares training centers, placement of the main companies specializing in this area of work and lists of vacancies in the main areas. The estimation of professional demand of graduates of Geoinformatics in the conditions of the modern market is given. Spheres of application of professional skills of graduates are considered, and also the main changes of the market of vacancies on the example of the North Caucasian Federal University are described. The results of the survey of students and graduates educated in the field of geoinformation technologies are presented. The process of employment of graduates of the North Caucasus Federal University in 2008 and 2016 for their specialization and priority of different areas of application of the knowledge in the field of Geoinformatics is considered in more detail. The opinion of experts on a number of professional issues was also taken into account. Conclusions: as a result of the study, it was possible to determine that the market of geoinformation products and services is undergoing a major transformation today. Geodetic sphere gives its leading position to modern navigation technologies. A large turnover of the market is observed in Western Siberia, Moscow and Leningrad regions, in addition to the Republic of Crimea. Along with this, regions such as the Krasnoyarsk territory are experiencing a signiicant shortage of specialists. The main share of graduates-Geoinformatics work by profession, their expectations during training often coincide with the real conditions of work after the University.